A dyadic perspective on assessment in Alzheimer's dementia: Supporting both care partners across the disease continuum. Issue 1 (28th August 2020) - Orsulic‐Jeras, Silvia; Whitlatch, Carol J.; Powers, Sara M.; Johnson, Justin
Abstract: Written from a dyadic strength‐based perspective, this article first provides a brief overview of the Education, Information, and Support section of the 2018 Alzheimer's Disease Dementia Care Practice Recommendations. 1 Subsequent sections present a comprehensive overview of available valid and reliable psychosocial measures that assess a selection of important domains for dementia care planning that can be used by families from early stage until end‐of‐life. Measures selected for the purposes of this article will focus on concepts that are strength‐based and most relevant to care dyads as they navigate the difficult disease trajectory: readiness, knowledge, coping, dyadic relationship, care values and preferences. We will also highlight measures that have traditionally targeted the family care partner but can potentially be considered for use with the care partner with dementia, with adjustments, beyond the early stages. Part of this discussion will include various strategies for including persons with dementia in all aspects of their own care using a strength‐based perspective, potentially enabling them to answer questions more reliably across disease stages. Last, gaps in existing measures will be identified to provide options to better assess areas of need most meaningful to families, and in ways that positively contribute to the successful aging of those living with dementia and their care partners.